Resective surgery for intractable epilepsy in children: radiologic evaluation. - Dietrich, R B; el Saden, S; Chugani, H T; Bentson, J; Peacock, W J (American Journal of Neuroradiology, 1991)
Epilepsy surgery is gaining popularity for the treatment of children with intractable seizures in whom either a focal or extensive unilateral structural brain lesion is demonstrated. We evaluated the pre- and postoperative imaging findings in 29 patients (aged 22 days to 19 years) who underwent hemispherectomies, 12 total and 17 subtotal. Pathologic correlation was obtained in all cases. Preoperatively, positron emission tomography and electroencephalography demonstrated abnormalities in all of the 28 children studied, but frequently could not characterize the lesion. CT or MR or both demonstrated focal or unilateral lesions in only 19 of these but gave additional information regarding the nature of the lesion. Preoperative angiographic findings were abnormal in five of 17 patients studied and were particularly useful in the evaluation of the extent of abnormality in patients with Sturge-Weber syndrome. Postoperatively, CT and MR demonstrated early complications such as the development of epidural blood and fluid collections, parenchymal hemorrhage, infection, and early hydrocephalus. Postoperatively, MR demonstrated the early development of septations, the presence of subarachnoid hemorrhage, and/or the deposition of hemosiderin in four patients, findings that historically have been associated with the development of devastating clinical complications. From these data, a recommended protocol of radiologic evaluation for patients undergoing hemispherectomy has been established.